CASE REPORTSAcquired hemophilia A as a cause of recurrent bleeding into the pleural cavity – case report and literature review - Wojtyś, Małgorzata; Żuk, Ewa; Alchimowicz, Jacek; Grodzki, Tomasz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2014)
Acquired hemophilia A is a coagulation disorder caused by autoantibodies against blood coagulation factor VIII. The first sign of this disease is often massive bleeding, which can affect patients after routine procedures. The parameter which indicates the presence of this condition is isolated prolonged activated partial thromboplastin time (APTT). The present article describes a case of a 32-year-old man with acute interstitial pneumonia and pleural effusion, in whom a massive hemothorax appeared after thoracocentesis; active bleeding was observed after the introduction of a chest tube. The patient was operated on, and no pinpoint bleeding was discovered during the procedure. Active bleeding was still taking place postoperatively. The patient underwent another operation after 6 days. Once more, no pinpoint bleeding was found. Prolonged APTT was observed. The activity of blood coagulation factor VIII was 3.04%. The presence of antibodies against factor VIII was confirmed, and acquired hemophilia was diagnosed. The article also includes an analysis of the literature on acquired hemophilia.